Patient and therapeutic radiographer experiences of comfort during the radiotherapy pathway: A qualitative study - Goldsworthy, S.; Latour, Jos; Palmer, S.; McNair, H.A.; Cramp, M. (2023)
Introduction: There is little research regarding the experiences of patient comfort and how it is best managed in radiotherapy. The aim of this study was to explore the experiences of patient and therapeutic radiographer views of comfort during radiotherapy. Methods: This qualitative study involved semi-structured interviews, with cancer patients (n = 25) and therapeutic radiographers (n = 25), conducted between January–July 2019. Patients were recruited from one radiotherapy clinic and therapeutic radiographers were recruited from across the United Kingdom via specialist interest groups and social media. Interviews were audio-recorded and transcribed verbatim. Thematic analysis was used to analyse the data separately between both groups and shared themes were identified. Results: Four themes were identified of which two themes were shared among both the patients and therapeutic radiographer. Emotional Health was a shared theme highlighting experiences such as stress, vulnerability and privacy. The second shared theme, Positioning and Immobilisation Experiences, concerned how patients’ experience being physically positioned and using immobilisation for accurate radiotherapy. The theme Information and Communication Experience was derived from patients highlighting concerns over sharing and provision of information and ways of communication. The last theme, Environmental Experience, emerged from the patient interviews and related to the first impressions of the radiotherapy environment such as reception or treatment rooms and how this effects the overall feelings of comfort. Conclusion: This qualitative study has provided the shared voice of patients and therapeutic radiographers and their experiences of comfort during radiotherapy. These shared experiences emphasise the importance of considering comfort holistically and not just from a physical context. This information can be used by therapeutic radiographers to better understand their patients experiences and needs to provide better comfort during radiotherapy to improve patients’ outcomes. Implications for practice: The clinical implications of our study can encourage Therapeutic Radiographers to provide holistic care for their patients throughout the pathway and specifically to comfort patients while they are having treatment. In the short term this could be via simple adaptions to practice while in the long term, research is needed to develop comfort interventions for patients receiving radiotherapy.